2017
DOI: 10.2139/ssrn.2925226
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Occupational Licensing Evidence from Detailed Business-Level Data

Abstract: The research program of the Center for Economic Studies (CES) produces a wide range of economic analyses to improve the statistical programs of the U.S. Census Bureau. Many of these analyses take the form of CES research papers. The papers have not undergone the review accorded Census Bureau publications and no endorsement should be inferred. Any opinions and conclusions expressed herein are those of the author(s) and do not necessarily represent the views of the U.S. Census Bureau. All results have been revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Thus restrictive licensing creates a barrier to mobility, misallocating workers across states. Thornton and Timmons (2013) add to this evidence by showing that the occupational regulation of massage therapist through state licensing appears to reduce the number of massage therapists, while Zapletal (2014) finds no effect of occupational licensing on the number of cosmetologists. Conrad and Dolan (1980) showed that reciprocity rules limit the migration of professions into restrictive states.…”
Section: Related Literature On Occupational Licensingmentioning
confidence: 98%
“…Thus restrictive licensing creates a barrier to mobility, misallocating workers across states. Thornton and Timmons (2013) add to this evidence by showing that the occupational regulation of massage therapist through state licensing appears to reduce the number of massage therapists, while Zapletal (2014) finds no effect of occupational licensing on the number of cosmetologists. Conrad and Dolan (1980) showed that reciprocity rules limit the migration of professions into restrictive states.…”
Section: Related Literature On Occupational Licensingmentioning
confidence: 98%
“…One approach is to use a flat opportunity cost such as the minimum wage. This is the method employed in Zapletal (2017) while investigating cosmetologist licensing. (The results presented below are qualitatively robust to this approach).…”
Section: Methodsmentioning
confidence: 99%
“…Recent work by Blair and Chung (2018) and Kleiner and Soltas (2019) suggests licensing reduces labor supply at the national level, aggregating across all occupations. Other works investigate these issues at the occupation level including massage therapists (Thornton and Timmons, 2013), cosmetologists (Zapletal, 2017), certified public accountants (Stephenson and Meehan, 2018) and dentists (Kleiner and Kudrle, 2000). Kleiner (2006) has a brief overview of the potential labor supply effects of licensing and reviews some previous empirical research.…”
Section: Introductionmentioning
confidence: 99%
“…Productivity Lowering overall service restrictions to an average feasible level of the three most deregulated EU economies would increase the productivity performance (in levels) of firms operating in both services and manufacturing industries by a maximum of 5.34 percent. Zapletal (2017) The Effects of Occupational Licensing Evidence from Detailed Business-Level Data…”
Section: Migration and Resources Allocationmentioning
confidence: 99%